The two-body strong decays of the fully-charm tetraquark states - Zhi-Gang Wang; Xiao-Song Yang (AAPPS Bulletin, 2024)
Abstract We study the hadronic coupling constants in the two-body strong decays of the fully-charm tetraquark states with the $$J^{PC}=0^{++}$$ J PC = 0 + + , $$1^{+-}$$ 1 + - , and $$2^{++}$$ 2 + + via the QCD sum rules based on rigorous quark-hadron duality. Then we obtain the hadronic coupling constants and partial decay widths therefore total decay widths, which support assigning the X(6552) as the first radial excitation of the scalar tetraquark state. And other predictions can be used to diagnose exotic states in the future.